Dual-Use Technology Jepang dan Kepentingan Keamanan Nasional Amerika Serikat - Roza, Rizky (Jurnal Hubungan Internasional, 2012)
The dynamic relations between Japan and the United States are interesting to be observed due to frequently happen in ânon-conventional â. Japan and America are two countries leading in the development of high technology, including military technology capabilities. The competition, both in the development of military technology often brings a unique and surprising relationship pattern. This paper shows that Japan continues to develop military technology that affects perception and capability of the country in the international political stage. On the other hand, the Japanese military technology development has given rise to responses from a number of countries in the region, as well as from major countries like USA. This paper shows that the achievement and the use of military technology will determine the future of the countryâs diplomacy with major countries in the world, especially the United States.